Determinants of R&D activities and performances of firms in Singapore manufacturing sector - Auw, Chor Khoon (2011)
Invention, innovation and technology play a big part in international competitive strategies of developed nations and in efforts by emerging nations to increase their standard of living. Quality-of-life standards are primarily related to science, innovation and technology, and are the direct results of organised research and development (R&D). Singapore has recognized that industry-driven R&D would contribute to current and future international economic competitiveness. The objectives for Singapore government to encourage and perform R&D activities are clearly spelled out in two technology plans. However, the determinant factors for private firms to perform R&D, and the contribute of R&D to firms' performances have not been comprehensively studied and reported.